Abstract Thought: Production of New Knowledge for the Development of Human Civilization - Shah, Krishma Prakash (Journal of Fine Arts Campus, 2021)
Abstract thought is the key source of new knowledge production for the development of human civilization. It is the mental state of being able to visualize or imagine beyond the physical world’s existence. Abstract thought has formed the basis of creativity, experimentation, and innovation. Analyzing ideas, creating information, solving problems, composing new ideas, and creating things are sources of new knowledge. So, the human abstract thinking process or thought is the result of new knowledge. New knowledge has always played a vital role in human advancement. The theory of empiricism is that all knowledge is based on experience derived from the senses. Transcendental idealism is another theory that is a term applied to the epistemology of German philosopher Immanuel Kant, who seized that the human self produces knowledge out of sense impressions. Transcendental is the ability to go beyond the usual limits; existence or experience beyond the normal or physical level is abstract. Kant attempts to synthesize sense perception and existing forms of the ideal realm above material reality. Abstract thoughts help people make it possible to imagine, visualize, and exercise to produce new knowledge. New knowledge plays a vital role in developing tools and new ideas that build up the quality of human life. This research theorizes that abstract thought is the root source of producing new knowledge for the development of human civilization. The core objective of this study is how abstract thought produces new knowledge. This study has focused on the imagination and visualization of the human thinking process to create new knowledge in art, science, and human civilization. The qualitative research model is adopted to analyze, interpret, and theorize this research paper.